CRITICAL DISCOURSE ANALYSIS ON THE PROGRAM OF INDONESIANLAWYER CLUB ON TV ONE IN THE PERSPECTIVE OF NORMAN FAIRCLOUGH ( Episode: Difficulty of The Execution of Jendral Susno Duaji) - Mukhroji, Muhamad (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2016)
This article reviews a criqlltical discourse analysis implementing Norman Fairclough perspective as the basis of analysis. There are three kinds of dimensions to analyze according to Fairclough, they are sentence structure, lexicon, and meaning. This article is a small report on a small CDA research by analyzing a television talk show, Indonesian Lawyer Club on TV One. The data are utterances recorded from the intercollutors in the event consisiting of nine parts of recording. They are Karni Ilyas, the host of the event, attorneys, Susno Duaji and his lawyer, and experts invited to the event. The research implemented critical discourse analysis especially based on Norman faiclough to uncover the implied meaning of the speaker. It was found that there were implicatures giving pragmatic force which were found in each recording which enabled watchers to understand the speaker meaning easily